Tri teze u društvu i tehnici - Cifrić, Ivan; Trako Poljak, Tijana (2013)
The paper investigates the development of society in the context of the development of technology. During the 20th century, a third subsystem, alongside nature and society, was formed – a technological system. The paper poses three theses on the role of technology in the relation between the two subsystems – nature and society – by examining its positive and negative impact on society. The theses are as follows: 1. Technology and its application have a dominantly positive impact on society and its development – technological optimism ; 2. Technology and its application have a dominantly negative impact on society and its development – technological pessimism ; 3. Technology and its application have both positive and negative impact on society and its development – the basis of anthropo-technological cohabitation. Each thesis is discussed as a social paradigm (orientation) during the course of human history. These paradigms are not historically successive but simultaneous, and they are closely connected with the ways in which society values technology. They reflect the so called ‚human nature paradox‛. The effect that technology and its application will have on a society depends on the type of the mediating role that a certain society expects from technology.
Projekt MZOS
HRV